Regular Running Is Related to the Knee Joint Cartilage Structure in Healthy Adults - Jandacka, Daniel; Casula, Victor; Hamill, Joseph; Vilimek, Dominik; Jandackova, Vera K; Elavsky, Steriani; Uchytil, Jaroslav; Plesek, Jan; Skýpala, Jiri; Golian, Milos; Burda, Michal; Nieminen, Miika T (Medicine and science in sports and exercise, 2024)
PURPOSE: The purpose of this study was to determine whether regular running distance and biomechanics are related to medial central femur cartilage (MCFC) structure. METHODS: The cross-sectional study sample consisted of 1164 runners and nonrunners aged 18-65 yr. Participants completed questionnaires on physical activity and their running history. We performed quantitative magnetic resonance imaging of knee cartilage-T2 relaxation time (T2) mapping (high T2 indicates cartilage degeneration)-and a running biomechanical analysis using a three-dimensional motion capture system. A 14-d monitoring of the physical activity was conducted. RESULTS: Those aged 35-49 yr were at 84% higher odds of having MCFC T2 in the highest level (85th percentile, P < 0.05) compared with youngest adults indicating that MCFC structures may be altered with aging. Being male was associated with 34% lower odds of having T2 at the highest level ( P < 0.05) compared with females. Nonrunners and runners with the highest weekly running distance were more likely to have a high T2 compared with runners with running distance of 6-20 km·wk -1 ( P < 0.05). In addition, the maximal knee internal adduction moment was associated with a 19% lower odds of having T2 at the highest level ( P < 0.05). CONCLUSIONS: Females compared with males and a middle-aged cohort compared with the younger cohort seemed to be associated with the degeneration of MCFC structures. Runners who ran 6-20 km·wk -1 were associated with a higher quality of their MCFC compared with highly active individuals and nonrunners. Knee frontal plane biomechanics was related to MCFC structure indicating a possibility of modifying the medial knee collagen fibril network through regular running.
Keywords: kloubní chrupavka; Magnetic Resonance Imaging; Sex Factors; magnetická rezonanční tomografie; Humans; lidé středního věku; běh; Female; Aged; mladý dospělý; dospělí; věkové faktory; Cartilage, Articular; senioři; lidé; sexuální faktory; femur; Adult; Knee Joint; Femur; ženské pohlaví; Male; Middle Aged; Adolescent; Cross-Sectional Studies; Young Adult; Age Factors; biomechanika; mužské pohlaví; Biomechanical Phenomena; průřezové studie; Running; mladiství; kolenní kloub